IMPLEMENTATION OF IN DEMONSTRATION METHODS TRADITIONAL GAME TO IMPROVE RUDE SOCIAL AND MOTOR SKILLS (Study of Semarak Sanggar ECD Students, Argamakmur) - Sutriana Sutriana; Nina Kurniah (UNIB Press, 2018)
The purpose of this study was to improve gross motor skills and social skills through traditional games in Semarak Sanggar Arga Makmur PAUD students. This study used Classroom Action Research (CAR) with implementation planning steps and reflection with the research subjects were 10 children in group B1. The data collection technique uses a child's observation sheet about gross social and motor skills. Analysis of research data using mean and t-test. The results showed that there were significant differences between gross social and motor skills through the application of demonstration methods in traditional games